Commissioned reports in Swedish healthcare governance - descriptive mapping and a content analysis - Anna T. Höglund; Erica Falkenström; Stefan Svallfors (BMC, 2022)
Abstract Background In order to support decisions regarding governance, organization and control models of the healthcare system, the Swedish government, as well as regional-level agencies, regularly commissions expert reports that are supposed to form the basis for decisions on new steering forms in healthcare. Aim The aim of this study was a) to perform a descriptive mapping of commissioned reports on Swedish healthcare governance and b) to pursue an in-depth content analysis of a strategic sample of such reports. Method Initially, 106 reports from both national and regional levels were gathered and analysed. A matrix was constructed, consisting of questions on who had commissioned the report, who had produced it, what problems the report set out to solve and what solutions were suggested. Further, questions were posed on whether the report was research-based and whether ethical assumptions and arguments were presented. Thereafter, a strategic sample of 36 reports was selected for an in-depth analysis, using inductive content analysis. Results The descriptive mapping showed that the aim of the analysed reports differed in form and content, and that they varied from giving an overview and investigating effects and consequences of new control models to more concrete goals, such as suggesting improvement measures. Academic experts involved in creating the reports often represented economics or business studies. The content analysis revealed examples of standardization in care, characterized by requirements to follow national guidelines, but also examples of requests for increased respect for professionals' competence and experience. Further, the analysis showed how the definition of equity in care had changed, from a focus on equity in access to care in the reports produced in the 1990s to an emphasis of arguments for geographical sameness and equity in quality of care in the later reports. Discussion Two dominant trends were identified in the material, namely increased standardization and arguments for trust in the system. The great number of reports implies that the system risks requesting more information than it can handle and result in documents where the same message is recurrently repeated or create conflicts of interest and value tensions between different suggestions. Conclusion Commissioned reports can have substantial consequences for new reforms of management practices in healthcare. It is therefore important to investigate them critically. The results of our investigation may contribute to a more comprehensive and adequate model for acquiring and using expert reports regarding healthcare governance, both in Sweden and in similar healthcare systems.